Meteorological determinants of bicycle traffic volume in Toruń - Różycka, Karolina; Pawłowski, Bogusław (Bulletin of Geography. Socio-economic Series, 2022)
This paper presents the results of research on the correlation between bicycle traffic volume (number of bicycles per day detected by counters) in Toruń and a selection of meteorological elements. The analysis covered the years 2019–21 and the data was sourced from the Municipal Roads Authority in Toruń and meteomodel.pl. Using IBM SPSS Statistics, models were developed to illustrate the influence of weather conditions on bicycle traffic volume in different periods of the year. The volume of bicycle traffic in Toruń was lowest in January (on average N=709 bikes recorded per day) and highest in July (N=4533). The period from June until September, during which the number of recorded bicycle passes was more than 2.5 times greater than in the remaining months of the year, was referred to as the ‘high season’. Amongst the analysed variables the strongest determinant of bicycle traffic was decidedly air temperature. However, in individual months, especially in summer, other weather elements also played a major part in affecting the so-called apparent temperature. This allowed for the identification of the weather-related preferences of cyclists in such months.